BIOCHEMICAL PROFILING OF PHYTONUTRIENTS FOR BREEDING NUTRIENT RICH POTATOES - Dalamu, Dalamu; Singh, Brajesh; Gupta, V K; Chopra, Shelly; Sharma, Reena; Singh, B P (Potato Journal, 2015)
Phytochemicals are bioactive non-nutrient compounds with protective or disease preventive properties. Considering the importance of phytonutrients, biochemical analysis of Indian potato genotypes with diverse skin and flesh colour was performed. Significant variations in total anthocyanin, carotenoids and phenolic content were observed in tuber flesh as well as whole tuber with peel, thus edifying potato as a potential source of phytonutrients. Potato peel which accounts for only about 10% of the sample total weight has been found to have significant nutritional composition. The genotypic variations were estimated to be about 20 fold for total anthocyanin, 3 fold for carotenoid as well as phenolic content. Higher magnitude of genotypic to phenotypic variance ratios for all the three parameters signify their transmission into next generation with lesser influence of environment on their accumulation due to minor difference between phenotypic and genotypic coefficient of variation. Out of thirty two diverse genotypes tested, eight were found to be excelling in all the three phytonutrients evaluated. The potential genotypes identified in the present study can be utilised as genetic base to breed novel fortified, coloured potato varieties. The alluring tuber flesh may variegate consumer’s plate with additional health benefits.